(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the synergetic and scientific foundations of Abu Rayhan al-Biruni’s natural philosophy. The research problem is not limited to describing al-Biruni as an encyclopedic scholar; rather, it asks how his reflections on nature, matter, motion, water, land, space and time can be interpreted as an early systemic vision of the natural world. Using qualitative textual analysis, historical-comparative reconstruction and the heuristic language of synergetics, the study identifies four interrelated mechanisms in al-Biruni’s intellectual heritage: the causal autonomy of nature, temporal depth of natural processes, transformative equilibrium of matter, and interdisciplinary synthesis of scientific knowledge. The results show that al-Biruni’s naturphilosophy combines empirical observation with philosophical generalization and therefore anticipates a relational understanding of nature as a complex, dynamic and self-organizing system. The article argues that a synergetic interpretation should not be understood as a direct attribution of modern theory to a medieval scholar; it is a methodological lens that reveals the systemic, non-linear and integrative structure of al-Biruni’s reasoning. The findings contribute to the history of science, philosophy of nature and contemporary studies of Central Asian intellectual heritage.